Surgical management of swimmer`s shoulder demonstrated poor correlation with preoperative magnetic resonance imaging findings - Etter, J.; Sharpe, K. (XIVth International Symposium on Biomechanics and Medicine in Swimming Proceedings, 2023)
INTRODUCTION One of the most common musculoskeletal complaints in competitive swimmers is shoulder pain. Some shoulders remain symptomatic after a full course of therapy consisting of scapular stabilization and posterior capsular stretching. The purpose of this paper is to describe one surgeon`s experience with arthroscopic management of swimmer`s shoulder and especially to describe differences in surgical and MRI findings. METHODS Over a 2 year period, competitive swimmers with painful shoulders who failed physical therapy and had clinical findings of instability underwent evaluation with MRI and subsequent arthroscopic evaluation. 16 shoulders in 13 patients required surgical management. RESULTS All 16 shoulders demonstrated pathology of the anterior inferior labrum. 12/16 had plastic deformation of the anterior inferior labrum and 4/16 had Bankart lesions (displaced tear of the anterior inferior labrum). There were also 14/16 with anterior inferior capsular laxity and 11/16 with a Type II SLAP tear. Only one MR arthrogram accurately described the pathology that was found at the time of arthroscopy. With surgical stabilization and appropriate physiotherapy, nearly all swimmers in this series were able to return to competitive swimming at prior or higher level of performance. DISCUSSION We found that swimmer`s shoulders which fail physical therapy generally have anteriorinferior laxity most often with plastic deformation of the labrum, which is not seen on MRI or MR Arthrogram. MR arthrogram findings consistently underestimated the pathology found at time of arthroscopy.